Exploration of the influence of body mass index on intra-network resting-state connectivity in chronic cigarette smokers. (1st October 2021) - Ely, Alice V.; Jagannathan, Kanchana; Spilka, Nathaniel; Keyser, Heather; Rao, Hengyi; Franklin, Teresa R.; Wetherill, Reagan R.
Highlights: Cigarette smokers show reduced resting-state functional connectivity within the salience network as BMI increases. Smokers show an inverted U-shaped relationship between BMI and default mode network rsFC. Heavier smoking is related to greater connectivity in the SN among lean and obese groups. Among the overweight group, heavier smoking is associated with reduced connectivity in the salience network. Abstract: Background: Obesity and cigarette smoking are two leading preventable causes of death. Previous research suggests that comorbid smoking and obesity likely share neurobehavioral underpinnings; however, the influence of body mass index (BMI) on resting-state functional connectivity (rsFC) in smokers remains unknown. In this study, we explore how BMI affects rsFC and associations between rsFC and smoking-related behavior. Methods: Treatment-seeking cigarette smokers ( N = 87; 54 % men) completed a BOLD resting-state fMRI scan session. We grouped smokers into BMI groups (N = 23 with obesity, N = 33 with overweight, N = 31 lean) and used independent components analysis (ICA) to identify the resting state networks commonly associated with cigarette smoking: salience network (SN), right and left executive control networks (ECN) and default mode network (DMN). Average rsFC values were extracted (p < 0.001, k = 100) to determine group differences in rsFC and relationship to self-reported smoking and dependence. Results: Analyses revealed a significant relationship between BMI and connectivity in the SN and a significant quadratic effect of BMI on DMN connectivity. Heavier smoking was related to greater rsFC in the SN among lean and obese groups but reduced rsFC in the overweight group. Conclusions: Findings build on research suggesting an influence of BMI on the neurobiology of smokers. In particular, dysfunction of SN-DMN-ECN circuitry in smokers with overweight may lead to a failure to modulate attention and behavior and subsequent difficulty quitting smoking. Future research is needed to elucidate the mechanism underlying the interaction of BMI and smoking and its impact on treatment.